Approaches towards improving the quality of maternal and newborn health services in South Asia: challenges and opportunities for healthcare systems - Naeem uddin Mian; Muhammad Adeel Alvi; Mariam Zahid Malik; Sarosh Iqbal; Rubeena Zakar; Muhammad Zakria Zakar; Shehzad Hussain Awan; Faryal Shahid; Muhammad Ashraf Chaudhry; Florian Fischer (BMC, 2018)
Abstract Background South Asia is experiencing a dismal state of maternal and newborn health (MNH) as the region has been falling behind in reducing the levels of maternal and neonatal mortality. Most of the efforts are focused on enhancing coverage of MNH services; however, quality remains a serious concern if the region is to achieve expected outcomes in terms of standardised MNH services within healthcare delivery systems. This research consists of a review of South Asian quality improvement (QI) approaches/interventions, specifically implemented for MNH improvement. Methods A literature review of QI approaches/interventions was conducted using the PRISMA guidelines. Online databases, including PubMed, the Cochrane Library and Google Scholar, were searched. Primary studies published between 1998 and 2013 were considered. Studies were initially screened and selected based upon the selection criteria for data extraction. A thematic synthesis/analysis was performed to organise, group and interpret the key findings according to prominent themes. Results Thirty studies from six South Asian countries were included in the review. Findings from these selected studies were grouped under eight broad, cross-cutting themes, which emerged from a deductive approach, representing the most commonly employed QI approaches for improving MNH services within different geographical settings. These consist of capacity building of healthcare providers on clinical quality, clinical audits and feedback, financial incentives to beneficiaries, pay-for-performance, supportive supervision, community engagement, collaborative efforts and multidimensional interventions. Conclusions Employing and documenting QI approaches is essential in order to measure the potential of an intervention, considering its cost-effectiveness, feasibility and acceptability to communities. This research concluded that QI approaches are very diverse and cross-cutting, because they are subject to the varied requirements of regional health systems. This high level of variability leads to implementation and knowledge-management challenges for MNH programme planners and managers in the countries of the South Asia region.